Strategi Guru Bimbingan dan Konseling Dalam Meningkatkan Pengamalan Ibadah Siswa - Inggra Fadhillah; Dodi Pasila Putri; Yeni Afrida (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
As for the background of the authors conducting this research is the existence of some students who have not prayed properly such as not hastening to the mosque or mushalla after the call to prayer, I did not do the tahiyyatul prayer before sitting, most students prefer to do other activities, many also learners who perform prayers by force and are still lazing in the classroom despite being reprimanded by the homeroom teacher, not a few students who still took time to the canteen. Application or process (deed) fulfill (obligation, duty). From the research carried out, it can be seen that the Guidance and Counseling teacher strategy in providing an understanding of the practice of the students' prayers has gone quite well by providing material about prayer in general to students in accordance with the material students have learned. The research method by the author is one of the descriptive qualitative field research. This research was conducted on students of class VIII at MTsN 2 Bukittinggi. The key informants were guidance and counseling teachers and supporting informants for PAI students and teachers. The author collects data with observation, interview and documentation techniques. Data processing techniques using qualitative descriptive analysis and techniques to test the validity of the data with data triangulation.